1960
DOI: 10.1002/cber.19600930115
|View full text |Cite
|
Sign up to set email alerts
|

Über α‐Halogenäther, IV. Synthesen aromatischer Aldehyde mit Dichlormethyl‐alkyläthern

Abstract: Aromatische Kohlenwasserstoffe geben mit Dichlormethyl‐alkyläthern bei Gegenwart von Friedel‐Crafts‐Katalysatoren in guten Ausbeuten die entsprechenden Aldehyde. Zur Darstellung der Chloräther im Labormaßstab wird ein einfaches Verfahren angegeben.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(92 citation statements)
references
References 21 publications
1
87
0
4
Order By: Relevance
“…Numerous formylation methods were developed to prepare diverse aromatic aldehydes from corresponding phenols [6], such as the Duff reaction [7][8][9], Vilsmeier-Haack reaction [10][11][12], Reimer-Tiemann reaction [13][14][15], Gattermann-Koch reaction [16,17], Gattermann reaction [18,19], Rieche reaction [20][21][22], and paraformaldehyde/MgCl 2 reaction [23,24]. These methods possess their individual advantages, however, low ortho-selectivity of the most of these methods and poor yields sharply limited their application in industry [25].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous formylation methods were developed to prepare diverse aromatic aldehydes from corresponding phenols [6], such as the Duff reaction [7][8][9], Vilsmeier-Haack reaction [10][11][12], Reimer-Tiemann reaction [13][14][15], Gattermann-Koch reaction [16,17], Gattermann reaction [18,19], Rieche reaction [20][21][22], and paraformaldehyde/MgCl 2 reaction [23,24]. These methods possess their individual advantages, however, low ortho-selectivity of the most of these methods and poor yields sharply limited their application in industry [25].…”
Section: Introductionmentioning
confidence: 99%
“…13 C-NMR spectroscopy is especially suited to the task of checking for the formation of the isomeric p-quinones or the reduced porphyrin catechols during the purification steps. Investigations by Hollenstein and von Philippsborn showed that the carbonyl resonances of o-quinones are the strongest high-field shifted carbonyl reso-nances of six-membered cyclic ketones.…”
Section: Resultsmentioning
confidence: 99%
“…Both aldehydes were prepared by Rieche formylation [13] from the respective 1,4-dialkyl-2,3-dimethoxybenzenes (Scheme 3). Despite the high steric demand in the veratrol, aldehyde 21 was obtained in 60% yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the synthesis of 1,2-dialkylbenzene the Grignard reaction was carried out by the method of Tamao et al [16]. For the synthesis of 1,2-dialkylbenzaldehyde the formylation was followed by the method of Riche et al [17]. The synthesis of (C n ) 8 TPPH 2 (2a) was carried out by the method of Adler et al [18].…”
Section: Experimental Synthesesmentioning
confidence: 99%